Hands-on machine learning with Azure : build powerful models with cognitive machine learning and artificial intelligence /: build powerful models with cognitive machine learning and artificial intelligence. (2018) - Abraham, Thomas K; Shah, Parashar; Stirrup, Jen; Lehman, Lauri; Basak, Anindita
No abstract available